Duplex Kidney with a Segmental Solitary Cystic Dysplasia and Ureteric Atresia: A Rare Case - Bakal, Unal; Sarac, Mehmet; Tartar, Tugay; Poyraz, Ahmet Kursad; Kazez, Ahmet (Istanbul Training & Research Hospital, 2020)
Dysplastic kidney cysts are developmental cysts of the kidney. They are mostly multi-cystic, and usually involve the whole kidney. In addition, the segmental and solitary form is rare. A one-year-old boy with an antenatal ultrasound diagnosis of a left kidney cyst was followed-up. Postnatal ultrasound examination revealed a duplex left kidney with a cystic dilatation in the upper pole and a normal appearing parenchyma in the lower pole. The cystic lesion (10 x 10 cm) with an upper polar location that did not show any regression was excised laparoscopically. The ureter communicating with the cystic component of the kidney was not seen on the left side during laparoscopy. Histopathologic diagnosis was a cystic renal dysplasia. We present a very rare case of a duplex kidney with a solitary dysplastic cyst and ureteric atresia and discuss the diagnostic and therapeutic process.
Keywords: Duplex kidney; cystic dysplasia; ureteral atresia; children